FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRODUKTIVITAS DAN KONTRIBUSI PENGHASILAN TENAGA KERJA WANITA PEMETIK TEH DI PTP. NUSANTARA VI KAYU ARO KABUPATEN KERINCI PROPINSI JAMBI - Priyono, Basuki Sigit; Cahyadinata, Indra; Setiowati, Setyowati (Jurnal AGRISEP, 2008)
The research was conducted in PTP Nusantara VI Kayu Aro, Regency of Kerinci, Jambi  Province on July to August 2006. The respondents were daily fix employees (DFE) of female tea picker, research location was chosen purposively. Aims of the research are: to estimate the productivity level, income level and contribution level to the family income of tea picker female worker in PTP Nusantara VI Kayu Aro Regenci of Kerinci, Jambi Province. Sampling conducted by Simple Random Sampling, total samples are 102 respondents of 1,011 people population. Statistic analysis used in the research is Rank Spearman (rs) correlation test by reliability level 95% (a/2 = 0.025) and to examine the significance level used two tailed t-test. In order to describe the characteristic and income level were used central measurement or score average of whole respondents as categorizing used value rank (interval). Based on result and discussion of the research, average of work productivity of tea picker in PTP Nusantara VI Kayu Aro is 5.55 kg/h and average income of tea picker female worker that gained by picking tea is Rp. 727,637.27/months by contribution of 58.31%. Statistic analysis result by Rank Spearman correlation test has known that factors of responsibility family member, motivation, and perception to income has significant correlation to the productivity level of tea picker female worker in PTP Nusantara VI Kayu Aro. Factors of age, formal education, work experience and perception to company facilities have  not a significant correlation to the productivity level.